A Holistic Multi‐Scale Approach to Using 3D Scanning Technology in Accident Reconstruction. Issue 5 (21st April 2020) - Baier, Waltraud; Donnelly, Michael J.; Payne, Mark; Williams, Mark A.
Abstract: Three‐dimensional scanning and documentation methods are becoming increasingly employed by law enforcement personnel for crime scene and accident scene recording. Three‐dimensional documentation of the victim's body in such cases is also increasingly used as the field of forensic radiology and imaging is expanding rapidly. These scanning technologies enable a more complete and detailed documentation than standard autopsy. This was used to examine a fatal pedestrian‐vehicle collision where the pedestrian was killed by a van while crossing the road. Two competing scenarios were considered for the vehicle speed calculation: the pedestrian being projected forward by the impact or the pedestrian being carried on the vehicle's bonnet. In order to assist with this, the impact area of the accident vehicle was scanned using laser surface scanning, the victim was scanned using postmortem CT and micro‐CT and the data sets were combined to virtually match features of the vehicle to injuries on the victim. Micro‐CT revealed additional injuries not previously detected, lending support to the pedestrian‐carry theory.